Meaningful evaluation of rehabilitation and closure in the early stages of the mine life cycle - Tomlin, C.; Gimber, C. (Mine Closure 2023: Proceedings of the 16th International Conference on Mine Closure, 2023)
Historically, key closure risks have been studied during operations and then further assessed as cessation of mining approaches. Only in the past couple of decades or so has progressive rehabilitation and closure become an integral part of regulatory frameworks, sustainable mine planning and more recently, new project and development planning. It is now broadly accepted that the best closure outcomes occur when rehabilitation and closure are properly considered up-front, during the early stages of a mine development project and well before mining occurs. Increasingly, regulatory processes are requiring more diligence on closure planning early in the environmental impact assessment (EIA) and approvals process, rather than later during dedicated closure study phases. There is an opportunity to use the information generated during this phase to make better decisions on project selection, design, mining methodology and all other facets of the mining operation. Incorporation of rehabilitation and closure risks and criteria in early project feasibility and planning phases can improve decision-making in order to reduce whole-of-life costs and maximise Environmental, Social and Governance (ESG) benefits. Whilst typically option assessments and Multi-Criteria Analyses (MCAs) touch on high-level closure considerations, mining options and mine design development are rarely based on future, detailed progressive rehabilitation and closure requirements. Furthermore, preliminary costings for these activities are often largely underestimated. Implementing meaningful closure considerations in the options selection process can lead to many benefits that may result in a change to the project design (including location of infrastructure and activities), construction methodology, complexity of approvals pathway/processes and operational procedures. This paper explores ways in which rehabilitation activities and closure options and costs should be considered in upfront project planning and decision-making processes to minimise long-term costs and residual liability.